(untitled) (Hematology Meeting Reports, 2009)
The ubiquitin proteasome pathway plays a central role in controlling intracellular turnover of proteins regulating cell growth and survival, stress responses, apoptosis and cell cycle.1 Proteasome inhibitors were initially developed in order to investigate the mechanisms of cellular proteolysis; early studies, however, showed that these compounds induced apoptosis preferentially in tumor cells and were thus considered antineoplastic drug candidates. 2 The 20s core of the proteasome contains three major sites of proteolytic activity, including a chymotrypsin-like activity, a trypsin -like activity and a postglutamyl peptide hydrolyzing or caspase-like activity. Bortezomib is the first proteasome inhibitor that shown effective in the treatment of haematological malignancies such as multiple myeloma (MM), and mantle cell lymphoma. 3-4 This compound is a boronic acid derivative that inhibits proteasoma activity by reversible binding to the chymotrypsin- like site of the 20s subunit. 5 In order to further exploit proteasome inhibitors as antineoplastic agents, other synthetic or natural compounds were studied in vitro or in animal models.